KOMUNIKASI INTERNAL HUMAS PT PERTAMINA (PERSERO) DALAM MEDIA ENERGIA WEEKLY - Choerunnisa .; Tatik Yuniarti (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2015)
This study aims to analyze the internal communication is done by Public Relations of PT Pertamina (Persero) in Energia Weekly Media related efforts to form the image of the company. As we know that the internal media to help public relations convey the message from company’s management to the workers. The method used by the author in this research was descriptive qualitative research design. Data collection method used is in- depth interviews and literature study / literature. Results of this study explain that the Public Relations of PT Pertamina (Persero) is under the Corporate Secretary, who runs the internal communication within Energia Weekly Media is Public Relations in Media Pertamina is located in the Corporate Communications Division. In conducting its internal communications within Energia Weekly Media, Public Relations of PT Pertamina (Persero) has policies and operational procedures so that the message delivered in the Media Weekly Energia well received by workers at Pertamina. Authors came to the conclusion from this study is that internal communication activities conducted by Public Relations of PT Pertamina (Persero) is implemented affectively and fairly good. It can be seen from the use of any appropriate media for internal communications workers can apply corporate values in shaping a positive image of Pertamina.